The Effect of Innovation and Product Quality on Consumer Satisfaction - Fadillah, Muhammad Rizky; Ubaidillah, Ahmad Zulfahmi; Ratnawati, R. Aryanti; Acuviarta, Acuviarta (Adpebi International Journal of Multidisciplinary Sciences, 2022)
The development of the energy sector in Indonesia always experiences an increase in the amount of energy, the energy source will eventually run out. Coconut charcoal is a solution that can replace the role of energy whose amount cannot be renewed. Coconut charcoal is also a reliable solution to reduce coconut waste in Indonesia. This research was conducted to determine consumer responses regarding innovation, product quality, and consumer satisfaction in CV coconut charcoal products. Superior Agro and analyze how much influence innovation, product quality, on consumer satisfaction on CV coconut charcoal products. Superior Agro. The object of research in this study is CV coconut charcoal products. Superior Agro, This research uses associative and descriptive research methods with a quantitative approach, namely research that aims to determine the influence between two or more variables, with quantitative research whose description form uses numbers or numberics (statistics). The number of samples obtained using the slovin formula is 73 samples. Based on the analysis using SPSS, respondents' responses regarding Innovation had a mean value of 3.35. Respondents' responses regarding Product Quality had a mean value of 3.24. Meanwhile, respondents' responses regarding Consumer Satisfaction had a mean value of 3.38. There is an influence between product quality variables and partial Consumer Satisfaction variables. it is also known that the Variables of Innovation and Product Quality have a significant effect on the variables of Consumer Satisfaction. These results are supported by the results of research and testing that has been carried out.